Impact of resource-conserving technologies on productivity and greenhouse gas emissions in the rice-wheat system - Pathak, Himanshu; Saharawat, Yash S.; Gathala, Mahesh; Ladha, Jagdish K. (Wiley, 2011)
The rice‐wheat system is the main source of food and income for millions of people in South Asia. However, because of increasing pressure of biotic and abiotic stresses in response to soil degradation and changing climate, crop productivity and farmers' profits are on a downward trend. Recent efforts have attempted to develop and deliver resource‐conserving technologies (RCTs) with efficient and environmentally friendly tillage/crop establishment and water use compared with the conventional practices of farmers. No tool, however, is available to evaluate the RCTs quantitatively, particularly in terms of greenhouse gas (GHG) emissions and other environmental impacts. A simulation model, named InfoRCT (Information on Use of Resource‐Conserving Technologies), has been developed integrating biophysical, agronomic, and socio‐economic data to establish input‐output relationships related to water, fertilizer, labor, and biocide uses; GHG emissions; biocide residue in soil; and N fluxes in the rice‐wheat system. The model provided a comparative assessment of RCTs in yield, income, global warming potential (GWP), biocide residue index, and N loss. The assessment showed that mid‐season drying and no‐till systems increased income, and also reduced the GWP. The model could be used for assessing impact of crop management practices on productivity and GHG emissions in rice‐wheat systems. © 2011 Society of Chemical Industry and John Wiley and Sons, Ltd